비수술적 방법으로 치료한 후극부 단독 천공성 안외상 환자 1예 - 정상문; 임재석; 박동,Sang Moon Jeoung, MD, Jae Seok Im, MD, Dong Park, MD (Daihan angwa haghoi jabji, 2009)
목적: 후극부 단독 천공성 안외상 환자에서 예방적 광응고술과 항생제의 점안 및 전신적 투여 등 비수술적 방법으로 양호한 결과를 보였기에 이를 보고하고자 한다. 증례요약: 46세 남자가 작업 중 가위가 왼쪽 광대활 부위를 후하방에서 전상방으로 관통한 후 발생한 좌안의 비문증을 주소로 내원하 였다. 내원 당시 좌안 최대교정시력은 0.8, 안압은 10 mmHg이었다. 세극등검사상 전방에서 세포와 방수흐림은 관찰되지 않았으며, 안저검사상 황반부에서 하이측으로 3 유두직경 정도 떨어진 후극부에 3 유두직경 크기의 망막 및 맥락막열공, 공막천공, 유리체출혈이 관찰되었다. 병변이 후극부에 위치하고 있어 수술적 접근이 어렵고 수술로 인한 안내용물 탈출의 위험이 있어 우선 병변 주위에 예방적 광응고술을 시행하고 항생제의 점안 및 전신 투여를 시행하였다. 입원 후 경과관찰 중 후극부에 견인성으로 보이는 경미한 망막주름소 견이 보여 추가로 예방적 광응고술을 시행하였다. 치료 6개월 후 좌안 최대교정시력은 1.0, 안압은 16 mmHg이었고 안저검사상 특이한 변화소견이 보이지 않았다. Purpose: To report a case of isolated posterior pole-penetrating ocular injury treated by nonsurgical methods such as argon laser photocoagulation and administration of antibiotics. Case summary: A 46-year-old male visited the hospital complaining of floaters in his left eye which had occurred when his cheek was penetrated by scissors from the inferior posterior part to the superior anterior part while working earlier that day. Upon initial examination, his best corrected visual acuity (BCVA) in the left eye was 0.8, and his intraocular pressure (IOP) was 10 mmHg. No cells or aqueous flares were observed in the anterior chamber. Fundus examination was performed, and three disc diameter-large breaks of the retina and choroid, scleral rupture and vitreous hemorrhage were observed at the posterior pole three disc diameters away from the fovea. It was difficult to make a surgical approach as the lesion was situated on the posterior pole, and there was the risk of prolapse of the eye contents. Therefore, we first performed argon laser photocoagulation around the lesion and administered topical as well as and systemic antibiotics. After admission the patient was observed carefully as the tractional retinal fold was located at the posterior pole. Additional argon laser photocoagulation was performed. After six months of treatment, BCVA in the left eye was 1.0, IOP was 16 mmHg, and no pathologic change was observed on fundus examination. KCI Citation Count: 0